Illegal Fintech Lending (Review of Financial Services Authority Regulation Number: 77/Financial Services Authority.01/2016) - Ardhana, Adnan Septian; Kasim, Nur Mohamad (Damhil Law Journal, 2022)
This study discusses the effectiveness of the application of the OJK Number: 77 / POJK.01/2016 concerning Information Technology-Based Money Lending Services. This study uses normative juridical research (normative law research). Normative juridical research refers to legal norms contained in legislation, Court decisions, legal theory and scholar's opinions and norms that exist in society. The approach used in the study is a normative juridical approach, then the approach taken in this paper is the approach to legislation, case approach and conceptual approach. In the study concluded that there are five (5) factors that cause the ineffectiveness of the application of this regulation are as follows; 1). Legal factors; 2). Law enforcement Factors; 3). Factors of law enforcement means; 4). Community factors; 5). Cultural factors.